Exploring the effects of the use of Interactive Whiteboard on Teachers Professional Development in South African high schools - Mokoena, M. M.; Simelane-Mnisi, S.; Mji, A.; Coetzer, L. M. J. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The paper evaluates the effects teacher development in the use of the interactive whiteboard (IWB) when teaching. This comes as a result that technology continuously evolves and requires teachers using the interactive whiteboard to remain lifelong learners in the area of technology. More time and resources should be allocated to facilitate professional development of teachers and make teachers familiar with the interactive features of the IWB. A literature review approach in this paper highlights inputs from different writers and later discusses findings and provides recommendations from a South African perspective on professional teacher development in the use of IWBs. This paper takes the form of a qualitative method and as a result a case study research design was selected for this study. Data were collected by means of interviews and observations. Data were analysed using ATLAS.ti version 6.2. The education district involved in the study has 41 high schools with about 1457 teachers but only 36 high schools had the IWBs installed and functioning. A non-probability sampling called convenience method was used to sample the population and 23 teachers from 22 schools were sampled. The results show that challenges encountered by teachers relate to the ineffective training methods, lack of follow-ups sessions as well as the lack of on-going training. In a study conducted in Tshwane North district, South Africa, the following question was asked: How is the teacher professional development conducted on the use of IWBs in teaching and learning? The study further revealed that teachers received professional development on the use of IWB. However, it was found in this study that the trainining was not enough in terms of the duration, and that training was only about how to learn the technical use of the IWB. Most of the teachers reported that training took two hours in the afternoon, three months, twice a week, every Wednesday, and after school. The study further revealed that poor IWB development caused frustrations when teachers had to utilise the IWB in class. When effectively used, IWB add the visual impact, assist in the learning process, increase active participation and engagement, and creates excitement and a positive attitude to learning. We recommmed that professional teacher development in the use of IWB in both technical and pedagogical aspects be a priority for successful use of this technology in schools. In this regard adequate teacher development could assist in eliminating a trend where the IWB is used by teachers as a projector to show videos or books but promote the interactivity provided by the features of this tool. Keywords: Interactive whiteboard, Professional development, High Schools, South Africa
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Interactive whiteboard; Professional development; High Schools; South Africa; CD-I technology; Electronic program guides; Teaching--Aids and devices